2021
DOI: 10.21203/rs.3.rs-244765/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A decade of systematic camera trapping in two strictly protected areas reveals the demography of a Eurasian lynx (Lynx lynx) population in Central Europe

Abstract: Large carnivores are crucial for ecosystems but are increasingly threatened by human persecution and habitat destruction. Successful conservation of this guild requires information on long-term population dynamics through the demographic surveys. We camera trapped Eurasian lynx between 2009 and 2018 in two strictly protected areas in the Bohemian Forest Ecosystem, estimating sex-specific demographic parameters using spatial capture-recapture (SCR) models as well as the relative abundance index of its prey spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…This conclusion is in line with other studies in which the effects of humans were shown to outweigh those of large carnivores (Ciuti et al, 2012;Muhly et al, 2011;Proffitt et al, 2009). Our results accordingly indicate that, despite a high abundance of lynx in the study area (Palmero et al, 2021), the risk posed by this large ambush predator, unlike that posed by human activities, did not cascade down to measurable differences in browsing intensity.…”
Section: Browsing Intensity Under Lynx and Human Risk Effectssupporting
confidence: 92%
See 1 more Smart Citation
“…This conclusion is in line with other studies in which the effects of humans were shown to outweigh those of large carnivores (Ciuti et al, 2012;Muhly et al, 2011;Proffitt et al, 2009). Our results accordingly indicate that, despite a high abundance of lynx in the study area (Palmero et al, 2021), the risk posed by this large ambush predator, unlike that posed by human activities, did not cascade down to measurable differences in browsing intensity.…”
Section: Browsing Intensity Under Lynx and Human Risk Effectssupporting
confidence: 92%
“…The main tree species within the Bavarian Forest are Norway spruce ( Picea abies ), silver fir ( Abies alba ) and, European beech ( Fagus sylvatica ), with rowan ( Sorbus aucuparia ), sycamore maple ( Acer pseudoplatanus ), and birch ( Betula pendula , Betula pubescens ; Bayerische Staatsforsten, 2018; Cailleret et al, 2014) also present in abundance. Lynx is the main predator species in the area, with 1–2 lynx/100 km 2 in the BFNP (Heurich et al, 2015; Palmero et al, 2021). In 2015, a wolf pair became established in the area and in 2017, the first wolf pack since 1846 was confirmed.…”
Section: Methodsmentioning
confidence: 99%
“…Protecting these vital habitat patches is important to maintain healthy lynx populations, and to provide offspring that might populate neighbouring habitat patches (Palmero et al, 2021). Isolation can lead to genetic drift and potentially inbreeding effects (Bull et al, 2016), so it is important that habitat is not degraded further.…”
Section: Discussionmentioning
confidence: 99%
“…The Eurasian lynx was eradicated from the area in 1848 but reintroduced in the 1970s ( Wölfl et al 2001 ). Currently, the population is considered to be stable, with an estimated density of approximately 1–2 lynx/100 km 2 ( Heurich et al 2015 ; Palmero et al 2020 ). In recent years, wolves have been recolonizing the area.…”
Section: Methodsmentioning
confidence: 99%